Dazhu Hongjingtian Preparation as Adjuvant Therapy for Unstable Angina Pectoris: A Meta-Analysis of Randomized Controlled Trials - Man, Changfeng; Dai, Zhe; Fan, Yu (Frontiers in Pharmacology, 2020)
Objective: Dazhu hongjingtian (DZHJT, Rhodiola wallichiana var. cholaensis [Praeger] S.H. Fu) preparation as an add-on therapy has been applied to the treatment of angina pectoris. We aimed to evaluate the efficacy and safety of DZHJT as adjuvant therapy for the treatment of unstable angina pectoris (UAP). Methods: An extensive literature search was conducted on PubMed, Emase, Cochrane Library, Wanfang, CNKI, and VIP databases from inception to January 2019. Randomized controlled trials (RCTs) comparing DZHJT in combination with Western medicine with Western medicine alone were included. Two authors independently performed the literature search, data extraction and risk of bias assessment of included studies, and conducted the statistical analysis. Results: A total of 18 RCTs involving 1,679 patients were included in the meta-analysis. Adjuvant treatment with DZHJT significantly decreased ≥80% reduction in the frequency of angina attacks (risk ratio [RR] 1.57; 95% CI 1.36–1.81), weekly frequency of angina attacks (mean difference [MD] -1.03 times; 95% confidence interval [CI] -1.51 to -0.55), marked improved abnormal electrocardiogram (RR 1.46; 95% CI 1.23–1.74). In addition, DZHJT significantly reduced the whole-blood viscosity (MD -0.70 mPa.s; 95% CI -0.84 to -0.55), plasma viscosity (MD -0.28 mPa.s; 95% CI -0.38 to -0.19), serum level of fibrinogen (MD -0.67 g/L; 95% CI -0.79 to -0.54), thromboxanes B2 (MD -14.01 ng/L; 95% CI -20.86 to -7.15), and C-reactive protein (MD -1.48 mg/L; 95% CI -2.72 to -0.25). No significant differ¬ences in headache/dizziness (RR 0.72; 95% CI 0.31–1.67) were observed between two groups. Conclusion: Adjuvant treatment with DZHJT has an add-on effect in reducing angina pectoris attacks in patients with UAP. The beneficial effect may be correlated with regulating whole-blood viscosity, plasma viscosity, fibrinogen, thromboxanes B2, and CRP level. However, future well-designed prospective, randomized, double-blind placebo-controlled trials with large sample sizes are required to evaluate the evidence.